Accelerated stability study of a solution containing plant extract from Traditional Chinese Medicine (Research, Society and Development, 2021)
Traditional Chinese Medicine (TCM) is a science that has spent its thousands of years of existence aggregating knowledge of its practices, which are based on the principle of balancing yin and yang energies. Stability is the factor that determines the compatibility between the active principles with their excipients and packaging, when there is no such compatibility, the preservation of a formulation is directly affected. Therefore, the objective of this work was to carry out an accelerated stability study (0 to 6 months; 40 ºC, 25% UR) of a solution containing extract of six MTC plants, through physical-chemical (organoleptic characteristics, pH, density and viscosity) and microbiological (for fungi and bacteria) quality control tests, following the methodologies described in the Brazilian Pharmacopoeia 6th edition. The analysis of the chromatographic profile by HPLC was also performed. The results observed in the physicochemical evaluations carried out during the study period (6 months) demonstrated adequate stability in organoleptic parameters, pH and density. The observed viscosity was different from other works, but it is acceptable for solutions and remained stable during the analyzed times. In the evaluation by chromatography, there was evidence of degradation of the assets after time 1 month, not showing stability under the conditions of temperature and humidity used during the study. In the evaluation of microbiological quality, the growth of fungi or bacteria was not observed in the analyzed times.